Strengthening Literacy through Learning to Read with the Syllable Method - Sujarwoko Sujarwoko; Marista Dwi Rahmayantis; Suhartono Suhartono; Moch. Muarifin; Faisol Faisol; Sherly Nur Azizah; Alfika Fatkhiyatul Ilma (Dimar)
Literacy activities in Early Childhood Education (PAUD) can be implemented through reading learning activities. The objectives of implementing this Community Service are (1) to provide training with the theme of strengthening literacy by implementing reading learning with the syllable method, (2) to provide assistance when teachers carry out learning, (3) to conduct discussions after providing assistance to find out strengths and weaknesses. The implementation method is through three stages: preparation, implementation, and evaluation. Training is carried out by delivering topics: the concept of learning the reading method with the syllable method, pedagogical competence, and introduction to reading books with the syllable method consisting of 4 volumes and how to teach it. In mentoring activities, teachers are observed when implementing learning by applying the concepts obtained during training. Meanwhile, a discussion meeting after mentoring is held to evaluate learning and find solutions for follow-up. In general, the implementation of community service was successful. This can be seen from the optimal attendance during training, the enthusiasm of teachers when carrying out learning, and the enthusiasm of teachers in conducting discussions after mentoring.